Eleventh Hour Linux - Speake, Graham (Elsevier, 2011)
he 11th Hour Linux+ Study Guide is keyed to the XK0-003 revision of the CompTIA Linux+exam. This book is streamlined to include only core certification information and is presented for ease of last-minute studying. Main objectives of the exam are covered with key concepts highlighted.